2006
DOI: 10.1509/jmkg.70.4.019
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Avatars on Online Consumer Shopping Behavior

Abstract: An impediment to Web-based retail sales is the impersonal nature of Web-based shopping. A solution to this problem is to use an avatar to deliver product information. An avatar is a graphic representation that can be animated by means of computer technology. Study 1 shows that using an avatar sales agent leads to more satisfaction with the retailer, a more positive attitude toward the product, and a greater purchase intention. Study 2 shows that an attractive avatar is a more effective sales agent at moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
279
1
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 335 publications
(306 citation statements)
references
References 55 publications
16
279
1
10
Order By: Relevance
“…The more this feature is used, the greater the likelihood of a click-out. This implies the importance of Downloaded by [University of Nebraska, Lincoln] at 04:53 13 April 2015 30 OlbRICH and HOlsIng price within the purchasing process. Accordingly, our hypotheses regarding the direct shopping features (H5(a)-(g)) are supported for six of the seven direct shopping features.…”
Section: Results Of Logit Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…The more this feature is used, the greater the likelihood of a click-out. This implies the importance of Downloaded by [University of Nebraska, Lincoln] at 04:53 13 April 2015 30 OlbRICH and HOlsIng price within the purchasing process. Accordingly, our hypotheses regarding the direct shopping features (H5(a)-(g)) are supported for six of the seven direct shopping features.…”
Section: Results Of Logit Modelingmentioning
confidence: 99%
“…We also found that community members are more likely to make a click-out than ordinary users. This implies that community members are more profitable.KEY WORDS AND PHRASES: Clickstream data, online consumer purchasing behavior, social shopping, user-generated content, virtual community.Parallel to the increasing importance of the Internet as a shopping channel [30,77], the advent of Web 2.0 is rapidly moving the online landscape into a truly consumer-driven era [8,19,75]. Web 2.0 provides consumers with many methods of creating and sharing user-generated content (UGC) [23,58,80].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…these designs have also been evaluated in various application contexts, such as computer-aided learning [31] and electronic commerce [49,55,77]. a summary of empirical evaluations of anthropomorphic interfaces is provided in appendix a.…”
mentioning
confidence: 99%
“…this design may have also undermined the validity of the results because people may have very different experiences when actually interacting with an agent to perform a real shopping task. In a recent study by Holzwarth et al [49], participants were asked to interact with and evaluate humanoid agents designed to deliver product information in an online shopping Web site. However, these agents only helped shoppers customize a product rather than recommended what to buy.…”
mentioning
confidence: 99%